I have self-compassion so I feel sexy! Sexual satisfaction and self-compassion effects on self-esteem and body esteem - Kocur, Dagna; Jach, Łukasz; Berek-Zamorska, Magdalena; Kamińska, Paulina (Studia Psychologica: Theoria et praxis, 2023)
Body esteem, self-esteem, and sexual satisfaction influence people’s well-being so it is important to look for psychological factors that may contribute to their improvement. However, men and women differ in the factors that affect their body esteem, self-esteem, and sexual satisfaction. We analyzed links between men’s and women’s self-esteem, body esteem, sexual satisfaction, and self-compassion. The research involved 716 heterosexual participants (365 men and 351 women). All measured variables correlated positively; however, some correlations were stronger among women than among men. Mediation analyses revealed that sexual satisfaction directly affected women's body esteem but did not directly affect men's body esteem. Self-compassion and sexual satisfaction explained more variance in self-esteem and body esteem among women than among men. We explained observed differences in the contexts of the self-perception theory and the objectification theory.